Experiential Subsistence Learning: Researching the Transformative Moments in Motherwork - Rose Barg (Adult Education Research Conference, 2000)
In this paper I explore the learning and knowledge creation that takes place within the lived experience of motherwork through artful inquiry that includes storytelling, narrative and poesis.